High‐Quality Three‐Dimensional Nanoporous Graphene1. Issue 19 (28th March 2014) - Ito, Yoshikazu; Tanabe, Yoichi; Qiu, H.‐J.; Sugawara, Katsuaki; Heguri, Satoshi; Tu, Ngoc Han; Huynh, Khuong Kim; Fujita, Takeshi; Takahashi, Takashi; Tanigaki, Katsumi; Chen, Mingwei
Abstract We report three‐dimensional (3D) nanoporous graphene with preserved 2D electronic properties, tunable pore sizes, and high electron mobility for electronic applications. The complex 3D network comprised of interconnected graphene retains a 2D coherent electron system of massless Dirac fermions. The transport properties of the nanoporous graphene show a semiconducting behavior and strong pore‐size dependence, together with unique angular independence. The free‐standing, large‐scale nanoporous graphene with 2D electronic properties and high electron mobility holds great promise for practical applications in 3D electronic devices.